Establishing a combined optogenetic-electrophysiological method to characterize the activity of granule cells in the dentate gyrus of freely moving mice - Cnops, Vanja (2017)
Efforts to understand the role of the dentate gyrus have been hampered by the limitation of extracellular recordings to identify cell types. By combining extracellular recording with optogenetics, it has become possible to identify and characterize the activity of specific cell types. Here, we assessed the feasibility of this technique to identify granule cells of the dentate gyrus in freely behaving mice. We were able to detect units that responded to light stimulation with short latency and high reliability. Although the short latency suggested that units were directly activated by light stimulation, we could not exclude the possibility that they were indirectly activated postsynaptic neurons. We also detected voltage fluctuations after the light stimulus, which were presumably caused by photovoltaic artefacts and synchronous activation of multiple cells. We believe that optogenetic identification of granule cells could be a valuable technique provided that the uncertainty about the response latency is resolved.